Periodic solutions of monotone differential inclusions with fast and slow variables - Khatskevich, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study the solvability of a periodic problem for monotone differential inclusions and the behavior of its solutions as the parameter changes.